The relationship between sensation seeking and five personality factors in two age groups - Butković, Ana (Array, 2003)
The relationship between broad personality factors and sensation seeking has so far been explored mostly using Eysenck's personality theory as a theoretical framework or using only some of the factors from the five-factor model (mainly extroversion and opennes). The aim of this study was to explore the relationship between sensation seeking and five-factor personality model. Therefore the sample consisting of 151 children (63% female ; mean age 16, 84) and 266 adults (56% female ; mean age 45, 10) completed the Sensation Seeking Scale - Form V (SSS-V) and the Five Factor Personality Inventory (FFPI). Children completed the measures in their school settings, while adults completed them individually at home. The correlations between the SSS-V and FFPI have been calculated separately for the two subsamples (children and adults). Results show that the relationship between sensation seeking and five personality factors is different in those two subsamples. Also, the regression analyses show that sensation seeking of children can be better predicted from personality than the sensation seeking of adults.